Understanding the Deliberation Practice in a Controllership from the Performative Judgement Perspective - Russo, Paschoal Tadeu; Leandro, José Roberto; Borinelli, Marcio Luiz; Souza, Rodrigo Paiva (Organizações & Sociedade, 2022)
This research analyzed deliberation practice in a controllership, mainly the decision to replace a given budgetary practice by another, in light of performative judgements, in a big-sized company in São Paulo City, between 2017 and 2020. The research followed the interpretative design, and adopted the research-action strategy. Participatory observation, in-depth interviews (initial research stage) and documental analyses were the techniques applied to find evidences. The field zooming in and zooming out movements were used to describe the elements featuring this practice, by switching the theoretical lens to better understand the whole and the elements composing it. Data analysis followed the framework proposed by Bispo (2015). We have found four fragments of practices encompassing the material arrangements where deliberation takes place: financial management practice, accounting management practice, expense management practice and information technology management practice. Different from the accountability management mainstream, which assumes rationality driven by economic aims, we have observed that deliberation in the assessed controllership is boosted by the “rationality of becoming” as permanent flow. Such a rationality is collectively built due to practical wisdom and to the ability of making practical decisions that form wisdom and practical judgements. It simultaneously shows its fragility in comparison to what is expected from the economic paradigm, as well as its richness, by encompassing the pluralism and dynamics of the context it is inserted in.